2018
DOI: 10.1111/jcal.12247
|View full text |Cite
|
Sign up to set email alerts
|

Improving early prediction of academic failure using sentiment analysis on self‐evaluated comments

Abstract: This study presents a model for the early identification of students who are likely to fail in an academic course. To enhance predictive accuracy, sentiment analysis is used to identify affective information from text‐based self‐evaluated comments written by students. Experimental results demonstrated that adding extracted sentiment information from student self‐evaluations yields a significant improvement in early‐stage prediction quality. The results also indicate the limited early‐stage predictive value of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 31 publications
1
53
0
2
Order By: Relevance
“…Many studies have also claimed that ensembled methods, such as AdaBoost and Random Forest, usually perform better and more robust than single classifier [16]. Furthermore, Table 2 shows that deep learning models perform slightly better than AdaBoost under the same data condition, which is line with previous findings [16], [30], [50]. It is concluded that DNN is a promising method for building prediction models than traditional machine learning algorithms in education.…”
Section: Experimental Results and Discussion 1) Prediction Performsupporting
confidence: 85%
See 1 more Smart Citation
“…Many studies have also claimed that ensembled methods, such as AdaBoost and Random Forest, usually perform better and more robust than single classifier [16]. Furthermore, Table 2 shows that deep learning models perform slightly better than AdaBoost under the same data condition, which is line with previous findings [16], [30], [50]. It is concluded that DNN is a promising method for building prediction models than traditional machine learning algorithms in education.…”
Section: Experimental Results and Discussion 1) Prediction Performsupporting
confidence: 85%
“…Specifically, LVAE component mainly aims to learn the latent feature distribution of at-risk students and generate some at-risk samples for the purpose of obtaining a balanced dataset. Due to the outstanding prediction performance of DNN [16], [30], it has been applied to perform final prediction in order to explore whether the latent feature distribution of at-risk students learnt by LVAE component is helpful for accurately identifying and capturing at-risk students. Finally, the effectiveness and robustness of the proposed LVAEPre framework are verified through multiple sets of experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The valence and arousal model, often called the "circumplex model" of affect [40] is widely used in psychological and psycholinguistic studies [41]. In computational linguistics, this model is applied when the interest is in continuous measurements of valence and arousal rather than in the specific discrete emotional categories [42].…”
Section: Plos Onementioning
confidence: 99%
“…Except from predicting affective states and performance and explaining engagement, other studies employed multimodal data for other research objectives, as well, including modeling dialogue Grafsgaard, Lester, & Boyer, 2015;Worsley, 2018), idea creation (Furuichi & Worsley, 2018) or motivational intentions (Yu et al, 2018), assessing presentation skills (Chen et al, 2016;Ochoa et al, 2018) and predicting collaborative coordination/synchrony between the collaborating peers (eg, Grafsgaard, Duran, Randall, Tao, & D'Mello, 2018;Schneider & Blikstein, 2015;Stewart, Keirn, & D'Mello, 2018;Worsley, 2014). Furthermore, substantial work has been done in the area of providing feedback using data in one or more modalities (Pardo, Poquet, Martínez-Maldonado, & Dawson, 2017).…”
Section: Related Work: Utilizing Multimodal Data To Predict Learning mentioning
confidence: 99%